Comparison of smoking behaviors and associated factors between HIV-infected and uninfected men in Guilin, China: a case–control study - Yu, Yong; Xiao, Fuqun; Xia, Mengqiu; Huang, Liman; Liu, Xiaohu; Tang, Wenyu; Gong, Xue (Frontiers in Psychology, 2024)
BackgroundSmoking is highly prevalent among HIV-infected individuals and is associated with high morbidity and mortality. Studies on smoking among HIV-infected individuals in China, especially compared to uninfected individuals, are scarce.PurposeThis study aimed to investigate and compare the prevalence and factors associated with smoking between HIV-infected and uninfected men in Guilin, China.MethodsA survey was conducted among 1,395 HIV-infected men at Guilin Third People’s Hospital from June to December 2022, with a 1:2 age (±1 year) and education-matched control group of 2,790 HIV-uninfected men, whose data were collected from March to August 2023. Both groups completed an online questionnaire on smoking behaviors and relevant characteristics, with a comparative analysis of associated factors conducted using chi-square tests and multivariable logistic regressions.ResultsThe rates of former smokers were comparable between HIV-infected and uninfected men [12.3% (95% CI: 10.7–13.9%) vs. 12.0% (95% CI: 10.9–13.1%)], but the current smoking rate was significantly higher in the infected group than in the uninfected group [37.6% (95% CI: 35.2–40.0%) vs. 27.6% (95% CI: 25.9–29.3%), p < 0.05]. In both groups, the following factors were significantly associated with smoking: higher income, presence of chronic diseases, negative coping styles, lower social support, and having depression, anxiety, and suicidal ideation. Additionally, in HIV-infected men, the following factors were exclusively associated with smoking: heterosexual HIV transmission route, lower CD4+ T cell count, longer duration of antiretroviral therapy (ART), and drug use.ConclusionHIV-infected men had higher smoking rates than their uninfected counterparts, indicating that HIV diagnosis may be a critical timing to initiate behavioral changes and deliver smoking cessation interventions. Furthermore, multiple demographic, clinical, and psychosocial factors were associated with smoking, indicating the need to develop and implement comprehensive smoking cessation prevention and intervention programs.